2002
DOI: 10.1038/sj.onc.1205951
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen promotes sarcoma growth and suppresses the accumulation of tumor-infiltrating macrophages

Abstract: The specific functions of plasminogen, stromal plasminogen activator, stromal plasminogen activator receptor, and stromal plasminogen activator inhibitor in the progression of the murine soft tissue sarcoma, T241 were investigated. Negation of plasminogen to the tumor blunted the orthotopic growth of the sarcoma in syngeneic mice. The reduced tumor growth was associated with a dramatic increase in tumor-infiltrating F4/80-positive macrophages and a diminution of vessel density, but not with obvious differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 99 publications
(95 reference statements)
2
18
0
Order By: Relevance
“…These observations are consistent with the bellshape effect of PAI-1 observed in vitro in the aortic ring assay and in vivo, in a model of laserinduced choroidal neoangiogenesis . By demonstrating that in vivo PAI-1 effects on tumor development and vascularization are dependent on its concentration, our findings resolve apparently conflicting data indicating that PAI-1 can inhibit as well as promote angiogenesis (Soff et al, 1995;Bajou et al, 1998;Gutierrez et al, 2000;McMahon et al, 2001;Stefansson et al, 2001;Curino et al, 2002).…”
Section: Excess or Absence Of Pai-1 In The Host-inhibited Tumor Invassupporting
confidence: 68%
“…These observations are consistent with the bellshape effect of PAI-1 observed in vitro in the aortic ring assay and in vivo, in a model of laserinduced choroidal neoangiogenesis . By demonstrating that in vivo PAI-1 effects on tumor development and vascularization are dependent on its concentration, our findings resolve apparently conflicting data indicating that PAI-1 can inhibit as well as promote angiogenesis (Soff et al, 1995;Bajou et al, 1998;Gutierrez et al, 2000;McMahon et al, 2001;Stefansson et al, 2001;Curino et al, 2002).…”
Section: Excess or Absence Of Pai-1 In The Host-inhibited Tumor Invassupporting
confidence: 68%
“…The analysis, by its inherent design, is limited to studying changes in steady-state levels of mRNA, and changes in wound healing gene expression that manifest at the level of mRNA translation or post-translational protein modification will go unnoticed. However, the method can be easily extended to also address changes in protein expression levels and post-translational modifications (Knezevic et al, 2001;Curino et al, 2002; T Pedersen and A Curino, unpublished data). The LCM and cDNA array analysis successfully identified multiple genes whose mRNA levels have previously been shown to be altered during skin wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of keratinocytes from histological sections by LCM was performed essentially as described (Bonner et al, 1997;Simone et al, 1998;Leethanakul et al, 2000;Curino et al, 2002). Cryostat sections (6 mm) were prepared perpendicular to the longitudinal direction of the wound, and the sections were kept on dry ice, or at À801C, until they were subjected to LCM.…”
Section: Lcmmentioning
confidence: 99%
“…Other studies showed modest effects of uPA deficiency on tumor growth and angiogenesis. 40,41 Another approach taken was to use a defective adenovirus to express a murine ATF systemically, which prolongs mouse survival and prevents liver metastasis in a colon carcinoma model. 32 In this study, a significant reduction in tumor angiogenesis and increase in apoptotic index was observed, in contrast to that seen in the uPA À / À mice.…”
Section: Discussionmentioning
confidence: 99%